INTEGRATING MENTAL HEALTH LITERACY INTO CORRECTIONAL SETTINGS: STRATEGIES FOR ENHANCING HELP-SEEKING BEHAVIOR AMONG PRISONERS WITH EMOTIONAL INSTABILITY - Rabia Khaliq; Arhum Fatima; Kamran Sher; Muhammad Latif; Dr. Nazia Iqbal (International Journal of Contemporary Issues in Social Sciences, 2024)
Correctional settings often house individuals with complex mental health needs, including emotional instability. However, accessing mental health services within these settings can be challenging due to various barriers, including stigma and lack of awareness about available resources. This research article explores the integration of mental health literacy initiatives within correctional facilities as a strategy to enhance help-seeking behavior among prisoners with emotional instability. Drawing upon existing literature and empirical evidence, this article proposes practical strategies and interventions to improve mental health literacy among both prisoners and correctional staff, ultimately aiming to facilitate early identification and intervention for mental health concerns in this population.